Susceptibility of common herbaceous crops to Phytophthora cinnamomi and its influence on Quercus root rot in rangelands (European Journal of Plant Pathology, 2012)
The susceptibility to Phytophthora cinnamomi of four crops (wheat, oat, vetch, and yellow lupin) commonly planted in rangeland ecosystems in southern Spain was evaluated. By means of in vitro infection experiments, the presence of the pathogen into the roots of yellow lupin (symptomatic) and vetch (asymptomatic) was observed, but never into wheat and oat roots (asymptomatic). It was also demonstrated that yellow lupin stimulated the production of zoospores of P. cinnamomi. Vetch, wheat and oat did not stimulate zoospore production. Under controlled conditions, only yellow lupin induced an increase in the number of viable chlamydospores in the soil. We concluded that the culture of wheat, oat, and vetch in rangelands did not influence the epidemiology of the Quercus root disease, even when asymptomatically-infected vetch is grown, and these crops can constitute an alternative to the culture of yellow lupin in rangeland ecosystems affected by Quercus root rot.